FAKTOR PENYEBAB TIDAK TERPENUHINYA KUORUM DALAM PILKADES E-VOTING DI DESA WARUNGPRING KABUPATEN PEMALANG TAHUN 2016 - Prabowo, Satya Agung; Astuti, Puji (Journal of Politic and Government Studies, 2018)
The development of technology also influences the running of governance and democracy, for example here is the emergence of e-ktp which then encouraged the emergence of the Election system using e-voting. The author here will examine the e-voting that has been carried out in Warungpring Village, Warungpring Subdistrict, Pemalang Regency in 2016, which in its implementation had a unique event, namely re-election because the DPT that was present did not fulfill the quorum in the Election validity requirements, so here the author will examine related to the cause of the event.To explain this research the author uses qualitative research methods by conducting in-depth interviews with relevant stakeholders such as the election village committee at that time and several urban village head in areas with high voter turnout and regions with low voter turnout. The method of data collection through literature study is by finding data in the place of the village electionÂ archive, namely in the Pemalang District Secretariat, in the Governance section. To examine the causes of unique events above the author uses three factors, namely political factors, economic factors, and administrative factors.The results of the research found that there were residents of the local community namely Warungpring villagers who did not like the prospective village head who was advancing in the Pilkades. Another finding was that there were some candidates for village heads who failed to run for office, some failed administrative tests and some failed medical tests.The recommendation that the writer can convey is that in the success of a general election good public participation is needed, and to realize a good community participation, contributions from all parties are needed from the electoral committee, the government, candidates who advance in elections, political parties, to the community itself must also actively contribute to creating good participation.